Floral Stimulation and Behavior of Insect Pollinators Affected by Pyraclostrobin on Arabica Coffee - Hagus Tarno; Karuniawan Puji Wicaksono; Edson Begliomini (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2018)
Coffee is the most valuable traded commodity after oil. On coffee, bees act to support a pollination that is shown by the number of harvested berries. This research aimed to evaluate the use of pyraclostrobin on flowering stage and insect pollinators on Arabica Coffee. Experiment was conducted in Kalisat Coffee Farm, Jampit, Bondowoso, ca. 1600 meters after sea level from October 2013 to April 2014. Randomized Block Design was adopted in this experiment. Three doses of pyraclostrobin and control were used as treatments such as 1.0, 1.5 and 2.0 cc L-1 of pyraclostrobin, and repeated three times. Percentage of fallen flower, fruiting stage, fruit production, frequency of bee`s visitation, and bee`s behavior was observed as variables in this experiment. Results showed that 1) percentage of fallen flowers was reduced by applying pyraclostrobin at 1.5 and 2.0 cc L-1 up to 50 % compared to control, 2) flowering rate was faster than control at 1.5 and 2.0 cc L-1 of pyraclostrobin, 3) application of 1.5 – 2.0 cc L-1 of pyraclostrobin increased the number of young fruits and pinheads, and 4) pollinators preferred to visit flowers of coffee trees which sprayed by pyraclostrobin than control treatment especially Apis mellifera.